2020
DOI: 10.1590/s1678-9946202062003
|View full text |Cite
|
Sign up to set email alerts
|

An exceptional case report of disseminated cryptococcosis in a hitherto immunocompetent patient

Abstract: Cryptococcosis is an opportunistic fungal infection causes significant disease predominantly in immunocompromised patients. Here we present an excepcional case of disseminated cryptococcosis with pulmonary and cerebral involvement in an immunocompetent patient with no apparent predisposing factors at the time of hospital admission. We described a case of an apparently immunocompetent 66-years old man admitted to hospital with a one-month history of cough, fever and vertigo. During hospitalization, thorax imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…et al, 2015 [ 30 ] Korea 33 to 73 years old Retrospective study 2003 to 2014 18 Presence of central vestibular signs allows bedside differentiation of isolated vestibular syndrome Parthasarathy R. et al, 2016 [ 31 ] Canada 76 years old Case report Not specified 1 Hypoperfusion to the flocculonodular lobe supplied by the anterior inferior cerebellar artery is likely a cause for intermittent vertigo Lee H. et al, 2002 [ 32 ] Korea 17 to 74 years old Prospective study March 2000 to July 2001 72 Migraine should be considered in the differential diagnosis of isolated recurrent vertigo of unknown cause Kim DD. et al, 2019 [ 33 ] Canada 60 s years old Case report 2019 1 Chronic naturopathic over- the-counter products intake may cause a subacute progressive cerebellar syndrome manifesting also with vertigo Adzic-Vukicevic T. et al, 2019 [ 34 ] Serbia 66 years old Case report 2019 1 Cryptococcosis may present even in immunocompetent patients and may show central nervous system involvement with vertigo Pula JH. et al, 2013 [ 35 ] USA 19 to 55 years old Prospective observational study 1999 to 2011 7 Multiple sclerosis is an uncommon cause of acute vestibular syndrome Kremer L. et al, 2014 [ 36 ] France, USA, UK, Japan, Canada, Germany Mean age 44.2 Prospective observational study Not specified 258 Br...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2015 [ 30 ] Korea 33 to 73 years old Retrospective study 2003 to 2014 18 Presence of central vestibular signs allows bedside differentiation of isolated vestibular syndrome Parthasarathy R. et al, 2016 [ 31 ] Canada 76 years old Case report Not specified 1 Hypoperfusion to the flocculonodular lobe supplied by the anterior inferior cerebellar artery is likely a cause for intermittent vertigo Lee H. et al, 2002 [ 32 ] Korea 17 to 74 years old Prospective study March 2000 to July 2001 72 Migraine should be considered in the differential diagnosis of isolated recurrent vertigo of unknown cause Kim DD. et al, 2019 [ 33 ] Canada 60 s years old Case report 2019 1 Chronic naturopathic over- the-counter products intake may cause a subacute progressive cerebellar syndrome manifesting also with vertigo Adzic-Vukicevic T. et al, 2019 [ 34 ] Serbia 66 years old Case report 2019 1 Cryptococcosis may present even in immunocompetent patients and may show central nervous system involvement with vertigo Pula JH. et al, 2013 [ 35 ] USA 19 to 55 years old Prospective observational study 1999 to 2011 7 Multiple sclerosis is an uncommon cause of acute vestibular syndrome Kremer L. et al, 2014 [ 36 ] France, USA, UK, Japan, Canada, Germany Mean age 44.2 Prospective observational study Not specified 258 Br...…”
Section: Resultsmentioning
confidence: 99%
“…Other possible etiologies are demyelinating disorders, VM and VN [ 32 , 36 , 37 , 46 , 47 ]. Lastly, isolated vertigo in adults can be associated with genetic disorders, malformations, vascular diseases or psychological illness [ 22 , 33 , 34 , 39 , 42 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our study, some previous studies reported extra-pulmonary cryptococcoses in HIV-negative patients from different world regions. [34][35][36][37] Moreover, in 64.71% of patients, no apparent underlying diseases were reported. This is nearly similar to previous studies from China, in which 71% and 60% of cases showed no apparent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Adzic-Vukicevic et al presented a case of a 66-year-old immunocompetent patient who presented with cough and vertigo whose chest imaging showed bilateral patchy opacities with nodules, initially concerning for metastasis, and subsequently became confused, had a lumbar puncture that was positive for Cryptococcosis. 7 Mada et al reported a case of a 56-year-old immunocompetent patient who presented with knee pain, magnetic resonance imaging (MRI) of the knee showed findings concerning for malignancy and pan-imaging showed a lung nodule, and fungal staining was positive for Cryptococcus neoformans . 8 …”
Section: Discussionmentioning
confidence: 99%